Analisis Faktor-Faktor yang Mempengaruhi Kinerja Karyawan Pada Natra Bintan a Tribute Portfolio Resort - Ardi, Muhammad Alvis; Putra, Trisna (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2023)
Employee performance in hotels is one of the factors that determine the development of a hotel. If the employee's performance is good, the company's goals will be achieved. But on the contrary, if the employee's performance is poor it will result in the service provided to guests not being optimal so that it will have a negative impact on the hotel. Therefore, employee performance is important to considered and researched in a company. One of the interesting hotels to research is Natra Bintan a Tribute Portfolio Resort. This type of research is quantitative research with a descriptive approach. The total of samples in this study is 84 people taken using saturated sampling techniques. The data collection technique uses a questionnaire arranged according to a Likert scale. Hypothesis testing uses factor analysis test with the help of the SPSS version 26 program. The purpose of this study is to analyze what factors influence employee performance at Natra Bintan a Tribute Portfolio Resort and analyze the factors that are most dominant in influencing employee performance at Natra Bintan a Tribute Portfolio Resort. The results of the study obtained the Kaiser Meyer Olkin test value (KMO) of 0.904 > 0.5 so that it can be stated that factor analysis is appropriately used to analyze the data obtained. Meanwhile, the results of the Barlett's Test of Sphericity state the results of significance at 0.000 <0.5 so that it can be concluded that there is a significant correlation matrix with a number of factors. Based on the total value of Variance Explained, there are 3 factors that are formed and have eigenvalues > 1 so that it can be concluded from this study that there are 3 factors that are formed, namely correlative factors, self-composition factors and working order factors that affect employee performance at Natra Bintan a Tribute Portfolio Resort.